Factores familiares de riesgo y protección del bullying en adolescentes de bachillerato en la zona Siete del Ecuador. - Brito Torres, Leonidas Gerardo (2017)
It is widely known that the phenomenon of bullyng is not new, although in the last decades it has transcended its study because in our computerized society through technology and social networks has spread its frequency and consequences in children and adolescents. As the research has progressed, it has been possible to establish different theories, risk factors, and prevention and intervention programs. The present work tries to establish the relation between the different familiar factors of risk and protection with the behavior of the bully (bully) of Zone 7 of Ecuador. It is intended to perform a non-experimental type of quantitative study; Whose design is of transversal type applying four instruments to detect the exposure to violence, locate bullies, establish the presence of support networks and family functionality to 960 adolescents who study the 1st. , 2nd. And 3rd. Year of baccalaureate of Zone 7 of Ecuador, comprised by the Provinces of El Oro, Loja and Zamora Chinchipe. Bullies vary in prevalence being more frequent in males. In addition a significant relationship is established regarding the exposure to intrafamily violence and being a spectator of violence transmitted by television. The family functionality has its influence on the relationship with the development of the phenomenon that is only explained in the case of men. The socioeconomic factor influences the development of the bullying phenomenon at higher stratum frequencies of adolescent’s bullyings.